Mengembangkan Tafsir Maqasidiy dari Maqasid Al-Qur’an - Syamsul Wathani (Lajnah Pentashihan Mushaf Al-Qur'an, 2025)
“Islamic education reform is carried out by discussing tarbawi tafsir. However, tafsir tarbawi so far has ontological problems written by education scholars, methodological problems with concise thematic interpretation models, and axiological problems in the form of interpretation results that tend to be conceptual, not providing actual answers to educational problems. In addition, maqasidiy interpretation of maqasid asy-syari'ah has a fundamental problem taken from the idea of usuliyun, and the limitation of interpretation is only used in legal verses. It is necessary to develop interpretation in the direction of progressive tarbawi interpretation by discouraging maqasidiy of maqasid Al-Qur’an. This article asks questions: How is the development of maqasidiy interpretation of maqasid Al-Qur'an? How is the progressive tarbawi interpretation of Surah Al-'Alaq (96): 1-5, and what is the significance of the interpretation? This article concludes: tafsir maqasidiy from maqasid Al-Qur'an is a development of tafsir methodology built on eight philosophical foundations derived from the Qur'an: straightening faith, improving morals, explaining the law, giving examples, inspiring and guarding education, giving good lessons, organizing social, and proving miracles. Maqasid Al-Qur'an becomes the philosophical foundation of the mufasir in developing meaning in the actual context. Progressive tarbawi interpretation of Surah Al-'Alaq (96): 1-5, among others: the unity of intellectual awareness and transcendental awareness, inspiring awareness of origin and blessings, being an optimistic foundation, teaching literacy awareness, and teaching humility. The significance of his tafsir affirms Islam as a religion that inspires education as a blessing for humanity and life.”